THE DPR'S RIGHT OF INTERPELLATION AND SUPERVISION OF THE PRESIDENT'S POLICY ON THE BAN ON THRIFTING IMPORTS OF USED CLOTHING : HAK INTERPELASI DPR DAN PENGAWASAN KEBIJAKAN PRESIDEN TENTANG LARANGAN IMPOR PAKAIAN BEKAS THRIFT - Iriani, Dewi (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2025)
The DPR as a representative and aspiration of the people can exercise the right of interpellation and oversight of the government. Oversight of the DPR is the President's policy which refers to the ban on thrifting imports of used clothing, causing upheaval in society. This policy is deemed not capable of realizing the concept of a rule of law state. So the problems are 1) What are the DPR's Interpellation Rights and oversight of the President's policy on the prohibition of Import Thrifting of used clothing? 2) What is the concept of an embodiment of the State Rule of Law on the prohibition of import thrifting of used clothes? This research methodology uses a normative review of the 1945 Constitution, Law no. 13 of 2019 concerning MD3 (MPR, DPR, DPD), Minister of Trade Regulation No. 18 of 2021 concerning Prohibition of Import of Goods. This research aims to find out the DPR's interpellation and oversight rights, the prohibition of the President's policy on the prohibition of Import Thrifting of used clothes. As well as knowing the concept of the rule of law state. Research results 1) The DPR can use the right of interpellation and supervision over the prohibition of Import Thrifting of used clothing by summoning and bringing together the government, used clothing traders, and clothing MSME traders to find a joint solution. 2) The DPR in realizing a rule of law state must be based on the rule of law, which is made for the welfare of the people and the common interest. Recommendation; The DPR not only oversees the government, but second-hand clothing traders are affected by the ban on finding other jobs.